Simplifying Cause Analysis : a Structured Approach. - Rowe, Chet (Rothstein Associates, Incorporated, 2017)
When the challenge is to get to the heart of a problem, you need a simple and efficient cause investigation methodology. And what would make a real difference would be an interactive map to lead you to the answer every time. Chester Rowe's Simplifying Cause Analysis: A Structured Approach is your instruction book combined with the included downloadable Interactive Cause Analysis Tool you have been looking for.